Protection and pragmatism: an exploration of the mentalities of workers in the private security industry - Weber, Ruby (Department of Public Law, 2018)
The quest for 'security' and the practices aimed at creating this on a literal and a figurative level is a common human striving. The people whom we task and entrust with providing this security are increasingly part of a combination of both public police and private security agents. Whilst the public police have been the focus of a large body of research, the volume of research in the field of private security is relatively thin. Given the robust growth of the private security sector in both developed and developing countries, combined with the dearth of research involving fieldwork in the private security industry, this research aims to fill a part of this knowledge gap. Specifically, this dissertation aims to address an even less-investigated research question - that of how the providers of private security think about and undertake their work of creating 'security'. In other words, it explores their mentalities. This exploration of the mentalities of those who provide private security will be undertaken through an exploratory case study, using the concept of nodal governance as the framing analytic. This case study focusses on a suburban security company operating in the southern suburbs of Cape Town, South Africa.